Some Considerations on the Genesis and Layers of Meaning of Road and Passenger Terms (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The terms "road" and "passenger" carry significant connotations in literature and cultural narratives, representing deeper layers of meaning beyond their literal interpretations. The genesis of these terms can be traced back to their symbolic roles in various contexts. The "road" often signifies a journey, choices, and the passage of time, reflecting the paths individuals take in life. It can also represent obstacles, challenges, and the pursuit of goals. Conversely, the "passenger" embodies the traveler or seeker, representing humanity's quest for purpose, identity, and understanding of one's place in the world. Together, these terms create a rich tapestry of meaning, inviting exploration of themes such as personal growth, transformation, and the interconnectedness of human experiences.